Combined Forward-Flyback-Converter with Only Two Diodes – Function and Modelling - Felix A. Himmelstoss; Helmut L. Votzi (Communications - Scientific letters of the University of Zilina, 2011)
A combined forward and flyback converter with a simple two windings transformer, an inductor, an active switch, two diodes and a buffer capacitor is explained. The voltage transfer ratio and the demagnetizing condition are derived. The voltage transfer ratio of the new converter is significantly higher compared to the forward and the flyback converters. The converter is useful for applications where a flyback converter is too small and a forward converter with its complicate transformer is too expensive. By shunting the two diodes by a third one the efficiency can be increased and due to the reduced losses the cooling is easier. The state space equations of the different states of the converter are derived.